2006
DOI: 10.1385/mo:23:2:171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Predictors of the Response to Neoadjuvant Anthracycline Chemotherapy in Locally Advanced Breast Cancer

Abstract: We found that tumors with large volumes, N2 node status, low cellular proliferation rate, positive immunoreactivity to p53, and low differentiation grade have a lower response to neoadjuvant chemotherapy with anthracycline. These patients could benefit from a different chemotherapy scheme to obtain a better control and resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
4
31
0
2
Order By: Relevance
“…While protein bound paclitaxel can be administered more quickly and is considered water-soluble [15,53], the underlying problems with side effects and damage to normal, healthy cells and tissues still remains. As such, treatment effectiveness is still based not only on cancer stage at diagnosis, but also patient responsiveness and the overall health of the patient [41,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…While protein bound paclitaxel can be administered more quickly and is considered water-soluble [15,53], the underlying problems with side effects and damage to normal, healthy cells and tissues still remains. As such, treatment effectiveness is still based not only on cancer stage at diagnosis, but also patient responsiveness and the overall health of the patient [41,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…The association between a high pCR rate and small tumor size has also been reported for anthracycline-based regimens (Fernandez-Sanchez et al 2006), suggesting that such an association is not speciWc to the chemotherapeutic regimen but merely indicates that small tumors are more likely to achieve pCR because of their small tumor burden. When tumors are divided into subgroups according to NG and tumor size, low-NG small tumors show a pCR rate as high as 30% for docetaxel, which is comparable to the pCR rate achieved by sequential therapy with anthrayclince-based regimens and taxanes.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, the lack of an association between Ki-67 expression and pCR seems to indicate that cell proliferation is not an important determinant of sensitivity to docetaxel. Interestingly, it has been reported that high NG and high proliferation are associated with a good response to anthracyclinebased regimens Vincent-Salomon et al 2004;Prisack et al 2005;Burcomber et al 2005;Fernandez-Sanchez et al 2006). It is clinically well established that taxanes and anthracycles are not cross-resistant and are eVective for diVerent spectrums of breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…13 e pathological response to the neoadjuvant chemotherapy provides reliable prognostic information. 13,14 e first prospective study for neoadjuvant chemotherapy in locally advanced, inoperable breast cancer is dated in 1973, by the European institute of Oncology and the primary purpose was to downstage the primary tumor in order to achieve surgical resection. 15 Many other trials followed in the past two decades studying the role of induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%